Cholinesterase measurements with an automated kit - Oliveira, G. H.; Henderson, J. D.; Wilson, B. W. (Wiley-Blackwell, 2002)
Background the Test-mate kit determines acetylcholinesterase (AChE, EC 3.1.1.7) and hemoglobin content of a drop of blood, displaying enzyme activities normalized to 25degreesC. Previous models produced inconsistent results at different temperatures. This report focuses on the current model, ChE 400, and two instruments of a previous OP model.Methods AChE activities were determined by the Ellman assay, using the three kits and a 96-well microplate reader Temperatures ranged from 10 to 37degreesC. Fetal bovine serum was the source of AChE.Results Normalized activities decreased below 20degreesC in the ChE model and below 25 C in the OP models. Activities of the same serum sample differed between the three Test-mate kits, ranging from 1.03 to 1.49 mumoles/min/ml. Percent errors were greater than with the microplate reader at all temperatures.Conclusions Neither we nor the manufacturer recommend the current Test-mate model for fieldwork. Nevertheless, there have been field measurements with Test-Mate kits, and we recommend that an enzyme activity standard be run in parallel with their use. (C) 2002 Wiley-Liss, Inc.
Keywords: test-mate; acetylcholinesterase determinations; accuracy and reliability; portable cholinesterase assay device